The Relationship between FDI, Exchange Rate, Financial Development and Trade in Goods and Services: The Case of China - Maimaijiang, Paerhati (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This thesis investigates the long run equilibrium relationship between FDI, exchange rate, financial development and trade in goods and services for the case of China between the years of 1982- 2016. The thesis applies unit root tests (Augmented Dickey-Fuller, Phillips – Perron and the Kwiatkowski–Phillips–Schmidt–Shin test) to test the stationarity of the variables, the VAR model, Johansen cointegration test to investigate the long run relationship between the variables, vector error correction model (VECM) in order to investigate the short term and long term relationship, Granger causality to determine the direction of FDI, financial development, exchange rate and trade in goods and services, impulse response function and lastly variance decomposition. VECM results shows a negative long term relationship between financial development and trade and also a long run positive relationship between exchange rate, FDI and Trade in the Chinese economy. The results of the thesis would guide policymakers in China to make efficient decisions in terms of the betterment of the Chinese economy.

ÖZ: Bu tez Çin’de 1982-2016 yılları arasında doğrudan yabancı yatırımlar, döviz kuru, finansal gelişim ve mal ve hizmet ticareti arasındaki uzun dönemli denge ilişkisini incelemektedir. Bu tezde, değişkenlerin durağanlığını test etmek için birim kök testleri (Augmented Dickey-Fuller, Phillips - Perron ve Kwiatkowski – Phillips – Schmidt – Shin testi), VAR modeli ve uzun dönemli denge ilişkisini araştırmak içinJohansen eşbütünleşme testi, kısa ve uzun dönemli ilişkiyi araştırmak için Vektör Hata Düzeltme Modeli (VECM)uygulanmıştır. VECM sonuçları, finansal gelişim ve ticaret arasında uzun vadeli ve negatif, doğrudan yabancı yatırımlar, döviz kuru ve ticaret arasında ise pozitif bir ilişki göstermektedir.Çalışmanın sonuçları Çin'deki politikacıların Çin ekonomisinin iyileşmesi açısından verimli kararlar vermesini sağlayacaktır.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2018. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Banks and Banking--Turkey; Investments, Foreign--China; Economic Conditions and Development--China; Exchange rate; Financial development; Foreign direct investments; Trade; China